Development of a quantitative food frequency questionnaire for use among rural South Africans in KwaZulu‐Natal. Issue 5 (7th October 2013) - Sheehy, T.; Kolahdooz, F.; Mtshali, T. L.; Khamis, T.; Sharma, S.
Abstract Background South Africa is experiencing a dietary and lifestyle transition as well as increased rates of noncommunicable chronic diseases. Limited information is available on the diets of rural populations. The present study aimed to characterise the diets of men and women from rural KwaZulu‐Natal (KZN) and develop a quantitative food‐frequency questionnaire (QFFQ) specific for this population. Methods A cross‐sectional study was carried out by collecting single 24‐h dietary recalls from 81 adults and developing a QFFQ in Empangeni, KZN, South Africa. Results The diet of this population was limited in variety, high in plant‐based foods (especially cereals and beans), and low in animal products, vegetables and fruits. Amaize meal staple (Phutu) was consumed by over 80% of subjects and accounted for almost 45% of energy intake, as well as making an important contribution to fat and protein intake. Most of the protein consumed by the study population was plant‐based protein, with almost 40% being obtained from the consumption of phutu and beans. A culturally appropriate QFFQ was developed that includes 71 food and drink items, of which 16 are composite dishes unique to this population. Conclusions Once validated, this QFFQ can be used to monitor diet‐disease associations, evaluate nutritional interventions and investigate dietary changes in this population.